Pengaruh Lama Penyimpanan Jamu Beras Kencur terhadap Pertumbuhan Kapang - Fransiskus Xaverius Agung Pinto Laksono; Ratih Dewi Dwiyanti; Rifqoh Rifqoh; Aima Insana (Jaringan Laboratorium Medis, 2022)
During the Covid-19 pandemic, people began to maintain their health, by using herbal medicine as an alternative treatment. One type of herbal medicine used is jamu beras kencur because it has properties to increase stamina, increase appetite, and relieve aches and cough disorders. In the Regulation of the Minister of Health of the Republic of Indonesia No. 007 of 2012 carrying herbs such as jamu beras kencur does not require marketing authorization. The quality of the herbal medicine produced has not been confirmed as feasible from microbial contamination, especially in molds, the number of yeast molds in the jamu beras kencur must comply with BPOM standards Number 32 of 2019 namely AKK 103 colonies/mL. This study aimed to determine the effect of the storage time of jamu beras kencur on mold growth with storage treatments of 0 hours, 4 hours, 8 hours, 12 hours, and 24 hours at room temperature. This type of research is a Quasi Experiment with a research design of One Group Pretest-Postest Design. The results of this study showed that the average AKK value was 0 hours 0.2x100 colonies/mL, 4 hours 0.4x100 colonies/mL, 8 hours 0.4x100 colonies/mL. 12 hours 0.8x100 colonies/mL and 24 hours 2.2x100 colonies/mL. These results stated that the jamu beras kencur met the BPOM standard requirements Number 32 of 2019 which was AKK 103 Colonies/mL. The results of the Kruskal Wallis test obtained a sig value of 0.286, it was concluded that there was no effect of storage time for the jamu beras kencur on the growth of molds. The identification results on the jamu beras kencur obtained fungal species, namely Aspergillus flavus, Aspergillus niger, and Penicillium sp. Suggestions for further researchers can examine the effect of storage time on mold growth in other types of herbal medicine.